2022
DOI: 10.3389/fimmu.2022.842189
|View full text |Cite
|
Sign up to set email alerts
|

Houttuynia Essential Oil and its Self-Microemulsion Preparation Protect Against LPS-Induced Murine Mastitis by Restoring the Blood–Milk Barrier and Inhibiting Inflammation

Abstract: Mastitis is a common inflammatory disease caused by bacterial infection to the mammary gland that impacts human and animal health and causes economic losses. Houttuynia essential oil (HEO), extracted from Houttuynia cordata Thunb, exhibits excellent antibacterial and anti-inflammatory properties. The aim of the study was to investigate the effects of HEO and a self-microemulsion preparation of HEO (SME-HEO) on inflammation and the blood–milk barrier (BMB) in lipopolysaccharide-induced murine mastitis. HEO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…HEO plays an anti-inflammatory role by blocking the activation of MAPK and other inflammatory signaling pathways, as well as the expression of iNOS. The authors concluded that HEO might provide a novel treatment for mastitis [133].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…HEO plays an anti-inflammatory role by blocking the activation of MAPK and other inflammatory signaling pathways, as well as the expression of iNOS. The authors concluded that HEO might provide a novel treatment for mastitis [133].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Studies have shown that allogeneic umbilical cord blood mesenchymal stem cell-derived exosomes alleviated subclinical mastitis in dairy cows [ 142 ]. Anti-inflammatory activity and protection of milk fat barrier integrity has been exhibited by small-molecule compounds in mastitis in recent years [ 143 , 144 , 145 ]. The determination of whether the use of bovine milk exosomes as the delivery vehicle of these small-molecule compounds for the treatment of mastitis can increase the efficacy of treatments and whether it presents a reasonable solution to problems of drug resistance and antibiotic residues in clinical practice remain.…”
Section: Application Prospects Of Exosomes As Drug Delivery Vehicles ...mentioning
confidence: 99%